2016
DOI: 10.21834/e-bpj.v1i3.373
|View full text |Cite
|
Sign up to set email alerts
|

Back Lanes as Social Spaces in Chinatown, Kuala Lumpur

Abstract: The back lane is often associated with annoying, disgusting, narrow and dark. This paper concerns the use of the back lanes of the old shop houses in China Town, Kuala Lumpur. The instruments used in collecting data include observation, unstructured interview and literature review. The use and physical characteristics of back lanes were identified. It was found that the back lanes of China Town in Kuala Lumpur showed the success of turning back streets into lively alleys. Thus, the back lane could be considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…On the other side, the facade designs, especially those that still retain Chinese shop houses' distinctive architectural features, are considered attractive and valuable (Puspitasari and Handjayani, 2016;Eddy et al). Narrow alleys as social spaces, spatial flexibility, and pedestrian-oriented designs give shop houses more value (Tirapas and Suzuki, 2013;Tirapas and Boonyachurt, 2013;Wan Ismail and Ching, 2016). Analysis of shop houses indicates that this typology is considered acceptable from the exterior and urban space aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other side, the facade designs, especially those that still retain Chinese shop houses' distinctive architectural features, are considered attractive and valuable (Puspitasari and Handjayani, 2016;Eddy et al). Narrow alleys as social spaces, spatial flexibility, and pedestrian-oriented designs give shop houses more value (Tirapas and Suzuki, 2013;Tirapas and Boonyachurt, 2013;Wan Ismail and Ching, 2016). Analysis of shop houses indicates that this typology is considered acceptable from the exterior and urban space aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A sociable street should accommodate street uses and activities, giving a quality outdoor environment for life on foot. A study by Wan Ismail and Ching (2016) explores that a variety of activities, pauses and experiences are the key to lively spaces and made a place to become attractive. Sholihah and Heath (2016) also observed that when the level of activities arises, the number of social activities also increases substantially.…”
Section: Street Role and Significancementioning
confidence: 99%
“…Studies have shown that a lively and dynamic street make people more aware of their surroundings. In some cases, people keep "eyes on the street" and indirectly alert of any unusual behaviour among the users (Nor Hanisah et al, 2016;Wan Ismail and Ching, 2016;Siti Aekbal et al, 2012). Therefore, a good street design is necessary to enhance the urban quality of life in so many aspects.…”
Section: Safety and Security Of Streetsmentioning
confidence: 99%
“…A sociable street should accommodate street uses and activities, giving a quality outdoor environment for life on foot. A study by Wan Ismail and Ching (2016) explores that a variety of activities, pauses and experiences are the key to lively spaces and made a place to become attractive. Sholihah and Heath (2016) also observed that when the level of activities arises, the number of social activities also increases substantially.…”
Section: Street Role and Significancementioning
confidence: 99%
“…Studies have shown that a lively and dynamic street make people more aware of their surroundings. In some cases, people keep "eyes on the street" and indirectly alert of any unusual behaviour among the users Wan Ismail and Ching, 2016;Siti Aekbal et al, 2012). Therefore, a good street design is necessary to enhance the urban quality of life in so many aspects.…”
Section: Visible Street Activitiesmentioning
confidence: 99%